2003
DOI: 10.1007/s00253-002-1100-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial silica deposition in geothermal hot waters

Abstract: A combined use of molecular ecological techniques and geochemical surveys revealed that thermophilic or hyperthermophilic microorganisms living in geothermal environments are likely to be implicated in the formation of biogenic siliceous deposits. Electron microscopic observations indicated that numerous microorganism-like fabrics were preserved in naturally occurring siliceous deposits such as siliceous sinter, geyserite, and silica scale, which suggests microbial contribution to silica precipitation. Molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Although microbially influenced corrosion at high temperatures has been poorly investigated, the microbial community investigated in this study might be associated with the formation of black rust. Based on the results obtained in this study, we propose the following process for black rust formation and the concomitant succession of the microbial community: (i) colonization of microorganisms that are indigenous to ridge flank crust and are transported by effluent crustal fluids (precipitation of silicate from the hot fluids might help the microbial colonization [27]), (ii) activity of sulfate reducers, including Ammonifex group bacteria, is stimulated by sulfate supplied from bottom seawater, and (iii) increased production of hydrogen sulfide creates reducing microhabitats where methanogens can grow. This process might explain the absence of detectable methanogens in the effluent fluids (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although microbially influenced corrosion at high temperatures has been poorly investigated, the microbial community investigated in this study might be associated with the formation of black rust. Based on the results obtained in this study, we propose the following process for black rust formation and the concomitant succession of the microbial community: (i) colonization of microorganisms that are indigenous to ridge flank crust and are transported by effluent crustal fluids (precipitation of silicate from the hot fluids might help the microbial colonization [27]), (ii) activity of sulfate reducers, including Ammonifex group bacteria, is stimulated by sulfate supplied from bottom seawater, and (iii) increased production of hydrogen sulfide creates reducing microhabitats where methanogens can grow. This process might explain the absence of detectable methanogens in the effluent fluids (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the expression of the sip, multidrug resistance ABC transporter and efflux pump genes in the presence of supersaturated silica and antibiotics As described above and in earlier papers (Inagaki et al, 2003;Doi et al, 2009), T. thermophilus strains TMY and HB8 promote silica deposition, cell adhesion and resistance to peptide antibiotics in the presence of supersaturated silica, all of which may be related with Sip production. Sip, the multidrug resistant ABC transporter and/or the efflux pump system in Thermus may participate in interactions between the cell surface and silicic acid and between the cells and inorganic materials for cell adhesion.…”
Section: Time (Hr)mentioning
confidence: 99%
“…For example, the siliceous deposits (called silica scale) formed on the surface of the equipment and in the pipelines at geothermal power plants have a significant negative economic impact related to energy loss and maintenance costs (Inagaki et al, 2003). Microscopic observation of these silicious deposits reveals numerous microbe-like structures, and it has been suggested that these fossils represent archaic microorganisms that grew in the hot, supersaturated fluids (Cook and Stakes, 1995;Yee et al, 2003;Handley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas prokaryotic organisms require a supersaturated silica environment to induce precipitation of amorphous silica during the exponential growth phase (Inagaki et al, 2003), eukaryotic organisms are able to accumulate silicate to concentrations that allow its polycondensation within their cell(s). Plants have the capacity to take up silicic acid in the range of 0.1 to 0.6mmoll -1 from the soil in their rhizosphere; they then translocate this monomeric ortho-silicic acid to their branches and deposit it as amorphous silica or poly(silicate), also termed biosilica (Morse, 1999;Müller et al, 2008e), in their cell walls (Ma, 2003) or in cell vacuoles (Neumann, 2003).…”
Section: Introductionmentioning
confidence: 99%